Methodology for Calculating Specific Expenditure of Acid Reagents for Filter Regeneration of Water-Well Intakes - V. V. Ivashechkin; E. A. Makarova; А. N. Kondratovich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The given paper proposes a methodology for theoretical calculation of acid reagent expenditure for dissolution of contaminative deposit of a unit mass having a known chemical composition.The methodology is based on the balance of substances in chemical reactions and interactions between hydrochloric acid and deposit components.